Efek Ekstrak Kasar Cacing Tanah Pheretima sp. terhadap Morfologi Sel Bakteri Salmonella enteritidis - Sahribulan, Sahribulan; Rauf H, Dirayah; Hasyim, Zohra (Fakultas MIPA UNM, 2018)
Abtract. This study was aimed at studying changes in the morphology of Salmonella enteritidis bacterial cells after the crude extract of Pheretima sp. using a scanning electron microscope (SEM). Earthworm extraction uses 96% ethanol, and binds to the appropriate bacteria in the exponential phase with extract concentrations of 5% and 10%. Observations using a microscope scanner were carried out after agreeing to a 6-hour, 12-hour, and 24-hour extract. Obtained from the results showing the crude extract of Pheretima sp. to changes in cell morphology of Salmonella enteritidis bacteria. Salmonella enteritidis bacterial cells are damaged consisting of: formed holes in the surface of bacterial cells, bumps on the surface of bacterial cells, shrinkage of bacterial cells, elongation of bacterial cells, and increase in bacterial cells. In addition, as well as longer contributions and free time, incubation, after being added, crude extract of Pheretima sp. against Salmonella enteritidis bacteria, the greater the damage caused. However, 5% extract concentration is the optimal concentration in the effect of damage to the morphology of the cells of Salmonella enteritidis bacteria.Keywords: Coarse Extract, Earthworms, Pheretima sp., Morphological Cells, Salmonella enteritidis, Scanning Electron Microscope (SEM).